2015
DOI: 10.1186/s12906-015-0836-8
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and apoptotic effects on cell proliferation of diosgenin isolated from Costus speciosus (Koen.) Sm

Abstract: BackgroundDiosgenin, a naturally occurring steroid saponin found abundantly in C. speciosus, is a well-known precursor of various synthetic steroidal drugs that are extensively used in the pharmaceutical industry.MethodsThe present study was conducted to evaluate the in vitro anticancer and apoptotic effects on cell proliferation of diosgenin isolated from C. speciosus (Koen.) Sm.ResultsThe results indicated that the treatment of HepG2 cells with the sample resulted in a cytotoxic effect as concluded from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 16 publications
0
42
0
4
Order By: Relevance
“…In fact, the anticancer effect of diosgenin has been studied in various tumoural cell lines and it was evidenced that this bioactivity depends both on the cell type and on concentration. Thus, for example, diosgenin has antiproliferative activity, namely, in prostate cancer (PC-3 and DU-145 cells) [23], colon carcinoma (HCT-116 and HT-29 cells) [24], erythroleukemia (HEL cells) [27], squamous carcinoma (A431, Hep2, and RPMI 2650 cells) [28], hepatocellular carcinoma (HepG2 and HCC cells) [6, 25, 29], gastric cancer (BGC-823 cells) [30], lung cancer (A549 cells) [31], breast cancer (MCF-7) [6, 3234], and human chronic myeloid leukemia (CML) (K562 cells) [1]. Moreover, several studies suggested that the known anticancer mechanisms of action of diosgenin are associated with a modulation of multiple cell signalling events involved in cell growth/proliferation, differentiation, epithelial-mesenchymal transition migration, and apoptosis, as well as oncogenesis and angiogenesis [12].…”
Section: Pharmacology: Recent Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the anticancer effect of diosgenin has been studied in various tumoural cell lines and it was evidenced that this bioactivity depends both on the cell type and on concentration. Thus, for example, diosgenin has antiproliferative activity, namely, in prostate cancer (PC-3 and DU-145 cells) [23], colon carcinoma (HCT-116 and HT-29 cells) [24], erythroleukemia (HEL cells) [27], squamous carcinoma (A431, Hep2, and RPMI 2650 cells) [28], hepatocellular carcinoma (HepG2 and HCC cells) [6, 25, 29], gastric cancer (BGC-823 cells) [30], lung cancer (A549 cells) [31], breast cancer (MCF-7) [6, 3234], and human chronic myeloid leukemia (CML) (K562 cells) [1]. Moreover, several studies suggested that the known anticancer mechanisms of action of diosgenin are associated with a modulation of multiple cell signalling events involved in cell growth/proliferation, differentiation, epithelial-mesenchymal transition migration, and apoptosis, as well as oncogenesis and angiogenesis [12].…”
Section: Pharmacology: Recent Datamentioning
confidence: 99%
“…Within the various phases of tumorigenesis, diosgenin seems to be critical in inducing apoptotic cell death and avoiding their malignant transformation [3, 5, 12]. More specifically, the diosgenin antitumor effects have been demonstrated, for example, to be mediated through p53 activation, immune-modulation, cell cycle arrest, modulation of caspase-3 activity, and activation of the transcription STAT3 signalling pathway [6, 7, 25]. In this context, important studies have shown that diosgenin inhibits the proliferation of osteosarcoma cells by inducing apoptosis and cell cycle arrest in G1 phase [35] and also inhibits the proliferation of breast cancer cells (MCF-7 cells) through the induction of the proapoptotic p53 protein and an increase of caspase-3 levels [6, 36].…”
Section: Pharmacology: Recent Datamentioning
confidence: 99%
“…Struktur kimia diosgenin Diosgenin (Gambar 2) adalah konstituen bioaktif yang sangat penting dalam herba pacing. Diosgenin berperan penting dalam aktivitas farmakologi seperti antihiperlipidemi (Son et al, 2007), antidiabetes (Ghosh et al., 2014), anti kanker (Selim and Al Jouni, 2015). Oleh karena itu, ada kebutuhan mendesak untuk mengembangkan metode sederhana untuk estimasi senyawa ini menggunakan instrumen canggih seperti kromatografi cair kinerja tinggi (HPLC).…”
Section: Pendahuluanunclassified
“…atau dengan menambahkan secara kuantitaif zat aktif pada produk obat (metode spiking). Akurasi dihitung sebagai persen perolehan kembali (recovery) dengan menetapkan jumlah analit yang ditambahkan ke dalam sampel, atau selisih antara rata-rata hasil pengujian dan nilai sebenarnya yang diterima (Anonim, 2009;Snyder et al., 2010). Dalam penelitian ini, uji akurasi ditentukan dengan menambahkan ejumlah standar diosgenin kedalam sampel (ekstrak CS).…”
Section: Uji Presisiunclassified
See 1 more Smart Citation